PLS-BASED INFERENTIAL MEASUREMENT OF FATTY ACID CONCENTRATIONS IN PALM OIL FRACTIONATION PLANT - H., Zabiri (2008)
Control of fatty acid concentration in the oleo-chemicals processing plants is a crucial step in ensuring a high quality product. A major difficulty in implementing Advanced Process Control (APC) systems in oleo-chemical fractionation columns is the difficulty in on-line measurement of the fatty acid concentrations. In this paper, Projection to Latent Structure (PLS) approach is used as a possible inferential method to predict the concentration of the different fatty acid fractions in the distillate of a palm-oil fractionating plant. Using real-life industrial data, results show that satisfactory predictions can be achieved using PLS.